Animals in Ritual and Economy in a Roman Frontier Community : Excavations in Tiel-Passewaaij - Groot, Maaike (2008)
This new volume in the acclaimed Amsterdam Archaeological Studies series explores the roles of animals in a rural community in the civitas Batavorum in the 1st to 3rd centuries ad. Large-scale excavations of two settlements and a cremation cemetery in Tiel-Passewaaij have yielded an animal bone assemblage of around 30,000 fragments. The study compares data from both the settlements and the cemetery, assessing the role of livestock in the local economy and the production of surplus products for the Roman market. The author also investigates the use of animals in funerary and other rituals. The inclusion of a catalogue of special animal deposits makes it a valuable reference work for animal bone specialists. Voor de kleine plattelandsgemeenschappen in Romeins Nederland vormde vee de basis van de plaatselijke economie en het dagelijks bestaan. Vee leverde voedsel, maar ook mest en trekkracht die nodig was voor de akkerbouw. Een surplus aan dierlijke producten werd geproduceerd voor de Romeinse markt. Daarnaast speelden dieren ook een belangrijke rol in rituele praktijken. Deze studie, die is gebaseerd op een grote hoeveelheid dierlijk bot uit grootschalige archeologische opgravingen in Tiel-Passewaaij, heeft verrassende nieuwe inzichten opgeleverd in zowel de economische als de symbolische aspecten van dieren.